Defense Economics, Industrial Base, and Management Strategy: A Bibliometric Analysis Using VOSviewer - Chhaeuy Samet; Hikmat Zakky Almubaroq; Yanda Dwira Firman; Deni Setiawati; Surachman Surjaatmadja; Irawati Irawati; Recky Recky (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
The purpose of this study is to use a bibliometric approach to examine the relationship between sustainable economies, industrial bases, and management practices. The method employed is a literature review and document analysis of scientific publication data from 2021 to 2025, which was studied using VOSviewer software. The study results show that the themes of management, markets, and industrial processes are the primary emphasis of the literature, with a high level of interconnectivity between variables. Network, overlay, and density visualizations show a movement in research topics from economics and markets to management strategies, industrial competitiveness, sustainability, and digital transformation. Despite generally consistent publication productivity, some critical subjects, such as risk management, human resource development, and industrial digitization, remain underexplored. This study emphasizes the necessity of taking an integrated strategy to building strategic industries that support sustainability, industrial resilience, and national independence in the face of increasingly complicated global dynamics